KONSEP USWATUN HASANAH DAN POLITIK (Studi Prilaku Tindak Pidana Korupsi Pejabat di Indonesia) - Muh. Haras Rasyid (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
Uswatun hasanah is derived from Arabic which means exemplary or a good example. This doctrine is closely related to the person's birth and mind or the nature and behavior of a person. Politics is concerned with power within an institution, region or country. The person of a person who holds political power or his or her leader in Indonesia can be an example to others around him. This paper departs from observations of reality and then examines how Uswatun hasanah practices existed in self of political power holder in Indonesia. Although there are still many leaders in Indonesia who behave well, but the number of abuses of corruption in particular by the state officials or leaders in this beloved republic, a clear indication that they (the person) does not instill uswatun hasanah to his subordinates in particular and the people of Indonesia in general.